EVALUASI PERTUMBUHAN JATI (Tectona grandis L.f) RAKYAT UMUR 15 TAHUN DI TROPIKA BASAH - Lia Rosiana; Yusanto Nugroho; Eva Prihatiningtyas (Universitas Lambung Mangkurat, 2020)
The purpose of this research was to evaluate the growth of teak plants in society humid tropicland at the age of 15 years (Ku II) and analyze the relationship between the growth of teak with the land bonita, physical and chemical properties of the soil. The results of the plant growth evaluation in society humid tropic at the age of 15 years (Ku II), identified in 3 land system i.e. LWW (Lawang uwang), TNJ (Tanjung), and PDH (pendreh) shows that the Tanjung (TNJ) land system provides the best growth results compared to LWW land system and the PDH. The best index of land bonita is on TNJ land systems which valued IV 1/2 at the age of 15 years with a height of 20,49 m, while the index of bonita land on PDH and LWW was 19.09 m high IV-19.21 m. The highly growth and bonita land index on land system TNJ supported by the chemical and physical properties of the soil tends to be better compared to PDH or LWW land system.Keywords: land system, bonita, society teak